Manufacturing high-performance flexible sensors via advanced patterning techniques - Xiaokun Qin; Bowen Zhong; Hao Xu; Joshua A Jackman; Kaichen Xu; Nam-Joon Cho; Zheng Lou; Lili Wang (International Journal of Extreme Manufacturing)
Sensors play an important role in information perception during the age of intelligence, particularly in areas such as environmental monitoring and human perception. To meet the huge demands for information acquisition in the whole society, the development of elaborated sensor structures using patterned manufacturing technology is important to improve the performance of sensors. Creating patterned structures can enhance the interaction between the sensitive material and target matter, increase the contact area between the sensor and the target matter, amplify the effect of target matter on the sensor structure, and enhance the density of information sensing by building arrays. This review presents a comprehensive overview of patterned micro-nanostructure manufacturing techniques for performance enhancement of flexible sensors, including printing, exposure lithography, mould method, soft lithography, nanoimprinting lithography, and laser direct writing technology. Meanwhile, it introduces the evaluation methods of flexible sensor performance and discusses how patterned structures influence this performance. Finally, some practical application examples of patterned manufacturing techniques are introduced according to different types of flexible sensors. This review also summarises and provides an outlook on the role of these techniques in enhancing sensor performance offering valuable insights for future developments in the patterned manufacturing of flexible sensors.